2016
DOI: 10.17523/bia.v73n1p53
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da produtividade diária de leite no impacto econômico da mastite em rebanhos bovinos

Abstract: RESUMO: Os objetivos desta pesquisa foram analisar e quantificar o efeito da produtividade diária por animal no impacto econômico da mastite em rebanhos bovinos leiteiros. A pesquisa foi realizada por meio de simulação no sistema computacional CU$TO MASTITE, considerando rebanhos leiteiros com produtividade média diária de 10; 20 e 30 litros de leite/dia. Foram consideradas como prevenção as despesas com monitoramento da incidência de mastite (cultura e antibiograma, contagem de células somáticas no tanque e c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 7 publications
0
11
0
11
Order By: Relevance
“…The higher percentage found in this study was due to management failures at two properties, resulting in increased medicinal costs to treat mastitis, leading to a maximum percentage of health spending (15.47%). Studies on the economic impact of mastitis have shown a clear need to prevent this disease because prevention is much cheaper than curative treatment (DEMEU et al, 2011;LOPES et al, 2011bLOPES et al, , 2012DEMEU et al, 2015DEMEU et al, , 2016.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher percentage found in this study was due to management failures at two properties, resulting in increased medicinal costs to treat mastitis, leading to a maximum percentage of health spending (15.47%). Studies on the economic impact of mastitis have shown a clear need to prevent this disease because prevention is much cheaper than curative treatment (DEMEU et al, 2011;LOPES et al, 2011bLOPES et al, , 2012DEMEU et al, 2015DEMEU et al, , 2016.…”
Section: Resultsmentioning
confidence: 99%
“…This is low, and whether only correcting and adjusting the property management is necessary or whether a greater investment in cow genetics is needed should be ascertained. Demeu et al (2016) stated that optimizing materials such as vaccines and materials for pre-and post-dipping affect the property's profitability because they do not change as a function of productivity. In seven production systems (25.93%), the average variable cost was higher than the milk's selling price; thus, ascertaining the breakeven point was impossible.…”
Section: Resultsmentioning
confidence: 99%
“…Essa baixa produtividade torna insustentável a permanência do agricultor na atividade ao longo do tempo, apresentando, dessa forma, baixa escala e produtividade (Fassio et al, 2006). A produtividade de leite, por animal, é um ponto importante para a tomada de decisões, pois influencia diretamente a receita e a lucratividade em rebanhos leiteiros (Demeu et al, 2016).…”
Section: Resultsunclassified
“…However, only 23% of the dairy farms used the CMT test (Table 3). The prevention of mastitis is very important, due to its high economic impact, estimated by Demeu et al (2016) at US$493.03, US$ 813.78, and US$ 1,134.53 per year per lactating cow at production rates production of 10; 20, and 30 L/day, respectively.…”
Section: The Use Of Electrified Fencing Occurred In 46%mentioning
confidence: 99%